2018
DOI: 10.1016/j.concog.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Musical hallucinations, musical imagery, and earworms: A new phenomenological survey

Abstract: HighlightsWe conducted a phenomenological survey comparing musical hallucinations to other inner music.MH were more likely to be reported as externally located than other experiences.MH were less controllable and less familiar than imagery or earworms.MH were less likely to include lyrical content than other forms of inner music.Individuals with higher levels of musical expertise were less likely to report MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…One paper that we retained following the initial literature search (Bailes, 2007 ) made no explicit differentiation between INMI and voluntary musical imagery, but is discussed in the present review on the basis of its seminal contribution in establishing a methodology for capturing musical imagery experiences in everyday life. In addition, some papers identified in the initial search examined broader or related phenomena, such as involuntary memories and musical hallucinations (e.g., Beaty et al, 2013 ; Floridou et al, 2018 ; Moseley, Alderson-Day, Kumar, & Fernyhough, 2018 ), but were retained for the review on the basis that they reported novel results on INMI specifically.…”
Section: Methodsmentioning
confidence: 99%
“…One paper that we retained following the initial literature search (Bailes, 2007 ) made no explicit differentiation between INMI and voluntary musical imagery, but is discussed in the present review on the basis of its seminal contribution in establishing a methodology for capturing musical imagery experiences in everyday life. In addition, some papers identified in the initial search examined broader or related phenomena, such as involuntary memories and musical hallucinations (e.g., Beaty et al, 2013 ; Floridou et al, 2018 ; Moseley, Alderson-Day, Kumar, & Fernyhough, 2018 ), but were retained for the review on the basis that they reported novel results on INMI specifically.…”
Section: Methodsmentioning
confidence: 99%
“…An interest in the topic has been rekindled within the last 20 years by several neuroimaging studies investigating the effects of music perception and imagery in the brains of both musicians and non-musicians (e.g., Zatorre, 1999;Lotze et al, 2003;Herholz et al, 2008). Recently, most references to musical imagery have focused on ''involuntary musical imagery'' (IMI, sometimes called ''earworms,'' ''sticky music,'' ''catchy tunes,'' or simply ''hooks''; e.g., Sacks, 2007;Farrugia et al, 2015;Williams, 2015;Moseley et al, 2018). However, in this article, we will focus on the ''volitional'' or active type of imagery of musical sounds and report a psychophysiological plus neuroimaging study on imagery, listening, and performance by a professional, internationally renowned, pianist.…”
Section: Musical Imagerymentioning
confidence: 99%
“…Consistent with this view, patients with VHs in Parkinson's disease have been shown to have elevated visual imagery strength compared to controls (Shine et al ., 2015). While some progress is being made in understanding musical hallucinations as misattributed ‘inner music’ (Fernyhough, 2016; Moseley et al ., 2018), it is more challenging to envisage an inner tactile sense (‘inner touch’) or inner olfaction (‘inner smell’) that could be misattributed to an external agency in the case of hallucinations. While voluntary and involuntary somatosensory and olfactory imagery (in the absence of actual sensations) are plausibly involved in typical human experience, these kinds of imagery remain only weakly understood from an empirical perspective, suggesting another way in which a modality-general approach to hallucinations might stimulate research.…”
Section: Misattribution Theoriesmentioning
confidence: 99%